الهوية العراقية بين صدع الاسم واستحالة الانتماء "رواية الحفيدة الأمريكية لإنعام كجه جي نموذجًا - خلوف, نهاد; جريوي, آسيا (جامعة الوادي - University of Eloued, 2021)
يعدّ مصطلح الهوية من المصطلحات التي لم ينته فيها القول إلى اليوم; إذ يثير مفهومها الكثير من الأسئلة النّقدية، ويحتل مساحة واسعة في التّمثيل السّردي الروائي. ولو أسقطناه على العراق لألفيناه يمثّل نموذجا حيا ؛ حيث تتوافر بلاد ما بين النّهرين على ماضٍ تاريخي على نحو غير عادي. وبالعودة إلى رواية الحفيدة الأمريكية لإنعام كجه جي نجد أن الرّوائية لم تغيب هذا المفهوم من خلال طرقها للانشطار الهووي الحاصل على مستوى الذات بدءا بالاسم، الذي يمثل دورا بارزا في تحديد هوية الفرد وصيانتها من التشرذم والابتذال، كما لم تُغيب مشكلتي الهجرة واللجوء وأثرهما على الانتماء، أين وجدت الذّات العراقية نفسها ضائعة بين مجموعة من الثقافات والحضارات واللغات، الأمر الذي هدد الخصوصية الثقافية والحضارية العراقية ولهذا تسعى هذه الدراسة إلى الكشف عن الانشطار الهوياتي الحاصل على مستوى الذات العراقية والمهدد لوحدتها وكينونتها.Abstract: The term identity is one of the terms that is still the subject of discussion to this day.Its concept poses several critical questions and covers a broad area of narrative novelistic representation.If we went back and dropped this on Iraq, we would have a living example of that, where Mesopotamia has an unusually historical past.When returning to Al-Hafeeda al-Amreekiya NovelforInaam Kachachi, we find that the novelist did not miss this concept through addressing the identity fraction at the level of the self, starting with the name.The latter plays a prominent role in identifying the identity and maintaining it from fragmentation and vulgarity.Inaam Kachachidid not miss as well migration and asylum, and their impact on belonging where she found the Iraqi identity lost among a range of cultures, civilizations, and languages. This threatened Iraq's cultural and civilizational specificity and, therefore, this study seeks to reveal the identity fraction that occurs at the level of the Iraqi self which threatens its unity and being.
Iraqi identity between the fracture of the name and the impossibility of belonging - Al- Hafeeda al-AmreekiyaNovel (The American Granddaughter) for InaamKachachi as a model-
مقال
Keywords: الانتماء، الاسم، الهوية، اللجوء، الذات، الآخر; name, identity, asylum, self, othe